Synthesis of tri-generation systems: Technology selection, sizing and redundancy allocation based on operational strategy - Andiappan, Viknesh; Ng, Denny K.S. (Computers & chemical engineering, 2016)
•New systematic approach to synthesise biomass-based tri-generation system.•Various operational strategies are considered.•Performs technology selection, sizing and redundancy allocation simultaneously. Tri-generation system is a facility which produces heat, power and cooling simultaneously from a single fuel source. In the industry, such system is commonly operated via two strategies; Following Electrical Load (FEL) or Following Thermal Load (FTL). However, these operating strategies may lead to huge amount of energy that is wasted. In this respect, several works have proposed a switching strategy, whereby tri-generation systems would interchange between FEL and FTL modes depending on energy demand. Unfortunately, the design of tri-generation based on this strategy has received limited attention. Besides, tri-generation operations often face challenges in equipment reliability. As tri-generation systems contain a network of interconnected equipment, equipment failures would disrupt the overall performance of a tri-generation system. As such, this work proposes a novel systematic optimisation approach to design a robust tri-generation system which can operate optimally in its operating strategies. In addition, the proposed approach can simultaneously determine type, size and required equipment redundancy (e.g. operating and standby units) of technologies while considering operating strategies in a tri-generation system. A palm biomass-based tri-generation system (BTS) case study is solved to illustrate the proposed approach.